Epidemiology of Pysichiatric Disorders - Ergashev Farrux Alijon ugli; Turdiev Pakhlavon Kakhramonovich (Scholars Digest Publishing, 2022)
This article presents the epidemiology of mental disorder of several diseases such as anxiety disorders, schizophrenia, depression, bipolar disorder, post-traumatic stress disorder, eating disorders, destructive behavior and dissocial disorders and disorders of the nervous system development. The number of these diseases is shown.
Keywords: schizophrenia, mental disorder, depression, nervous system.